Perilaku Oportunistik dalam Praktik Manajemen Laba dengan Nilai Akhlak sebagai Ethicality Judgment - Rimi Gusliana Mais; Munir; Fanisyah Maliki; Joko Bagio Santoso (Universitas Muhammadiyah Surabaya, 2024)
This study aims to examine how opportunistic behavior in earnings management practices with moral values ​​as ethical judgment in Islamic banking, especially in Bank Syariah Mandiri. This study uses a qualitative research method with a phenomenological approach where the phenomena that occur in Bank Syariah Mandiri will be examined both in its operational activities whether they are in accordance with Islamic sharia principles and analyzing the presentation of its financial statements whether they are disclosed fairly and transparently. Data acquisition was carried out through in-depth interviews with informants and internet searches as complementary data. The results of this study indicate that Bank Syariah Mandiri is a sharia bank that holds principles in accordance with Islamic values ​​so that it is not found to be practicing earnings management, let alone reflecting opportunistic behavior, but in Islamic banks it applies moral values ​​as the main reference in its operational activities, earnings management practices that are permitted if they avoid deviant behavior and are in accordance with PABU/GAAP. Then the presentation of financial statements is in accordance with PSAK 101 and includes the values ​​of truth, justice and honesty in it.